Role of Positive Thinking and Personality Traits in Predicting Satisfaction With Nasal Surgeries - Sattar Mahmoudi; Rasoul Gheisari; Mehrnosh Rabbanizadeh (Gonabad University of Medical Sciences, 2021)
Background: Rhinoplasty is recognized as a complicated, but common procedure. Although patient satisfaction with these surgeries is less commonly discussed, it is one of the most important determinants of surgical success. This study was done to predict the patients' satisfaction with nasal surgeries, based on their personality traits and positive thinking. Methods: This cross-sectional, descriptive, correlational study was conducted in Shiraz, Iran, during the fall and winter of 2017. A total of 200 individuals undergoing rhinoplasty were selected, using the convenience sampling method. The Rhinoplasty Outcome Evaluation-Revised (ROE-R) questionnaire, Automatic Thoughts Questionnaire-Positive (ATQ-P), and Neuroticism-Extraversion-Openness (NEO) personality inventory were used for data collection. The obtained results were analyzed by SPSS v. 23, using inferential statistics and stepwise regression analysis. Results: The results showed that satisfaction with nose fitness had a significant positive relationship with agreeableness and openness (P<0.01). Also, the overall satisfaction with surgery had a significant positive relationship with these personality traits, while a significant negative relationship was found with neuroticism (P<0.01). Moreover, the results showed that positive thinking and personality traits could predict 6% of changes in the overall satisfaction with surgery (P<0.001). Neuroticism showed an inverse correlation with satisfaction (P=0.001, β=-0.24). Conclusion: Regarding the relationship between satisfaction with rhinoplasty and personality traits, it was found that different personality traits are associated with different attitudes, influencing surgical outcomes, and satisfaction.